Amelioration of Paracetamol-Induced Hepatic Damage by Aqueous Extract of Curcuma Caesia in Rat - Kumar Gour, Jay; Jain, Sandeep; Chauhan, Pradeep (Journal of Neonatal Surgery, 2025)
Man's inventiveness is demonstrated by the usage of plants to heal specific illnesses. There are numerous reports of Curcuma caesia, sometimes referred to as kali haldi in Hindi, being utilized as a treatment for a variety of illnesses. The aim of this study was to assess the potential of a flavonoid-rich extract of the entire Curcuma caesia plant to mitigate the hepatotoxic effects of paracetamol on mice. Total phenolics were determined using phytochemical screening and extraction in a variety of solvents. The aqueous extract of Curcuma caesia was utilized to investigate the preventive effect on hepatic damage caused by paracetamol. 7.97%w/v of the aqueous extract and 12.36%w/v of the methanol extract were produced. The aqueous extract was found to contain alkaloids, glycosides, phenolics, flavonoids, carbohydrates, saponins, sterol, and terpenes, according to the phytochemical screen. It was discovered that the methanolic and aqueous extracts had total phenolic contents of 63.17 and 78.54 GAE mg/g of dry extract, respectively. In contrast to the group that received PCM, the biochemical analysis unequivocally shows that the hepatic cells in the group treated with an aqueous extract of Curcuma caesia (50 and 100 mg/kg, p.o.) are normal. Because it may restore the liver function that has been damaged by PCM, the aqueous extract of Curcuma caesia can be regarded as an effective hepatoprotective in nature. Therefore, it was determined that Curcuma caesia extract has hepatoprotective properties